2013
DOI: 10.1080/00986445.2012.751377
|View full text |Cite
|
Sign up to set email alerts
|

Gas Absorption in Stirred Gas-Liquid-Liquid Systems: Effect of Transferred Solute Solubility and Oil Phase Spreading Characteristics

Abstract: The effect on gas-liquid mass transfer of dispersing an oil phase in water in an aerated stirred tank is not predictable, because the mechanisms involved are not well understood. To try to elucidate these mechanisms, a set of experiments was carried out that included: (i) measurement of the effect of oil addition on gas dispersion properties, (ii) quantification of mass transfer of two solutes (heptane and oxygen) with very different solubilities in the liquid phases, and (iii) variation of the spreading chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 33 publications
1
10
2
Order By: Relevance
“…Experimental values of k L a obtained under these conditions of agitation were in fact not used in obtaining parameters for expressions (13)-(15) (Alves and Pinho, 2013). Figures 11 and 12 extend the range of simulations of E ¼ f(/), to higher and lower values of agitation speed N (at constant aeration v S ) and to higher and lower values of v S (at constant N).…”
Section: Non-spreading Systemmentioning
confidence: 95%
See 2 more Smart Citations
“…Experimental values of k L a obtained under these conditions of agitation were in fact not used in obtaining parameters for expressions (13)-(15) (Alves and Pinho, 2013). Figures 11 and 12 extend the range of simulations of E ¼ f(/), to higher and lower values of agitation speed N (at constant aeration v S ) and to higher and lower values of v S (at constant N).…”
Section: Non-spreading Systemmentioning
confidence: 95%
“…In a recent experimental study, Alves and Pinho (2013) studied oxygen absorption in a stirred tank with both spreading (heptane) and non-spreading (dodecane) dispersed oil phases and found that E varies with oil holdup, /, in a significant different manner, as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…n-hexadecane) negatively or hardly affect k L a , although at lower vector concentrations k L a may increase due to the shuttling effect, through which vector droplets briefly contact the air bubble surface and subsequently transfer oxygen to the bulk aqueous phase (Alves & Pinho, 2013;Quijano & Hernandez, 2010). n-hexadecane) negatively or hardly affect k L a , although at lower vector concentrations k L a may increase due to the shuttling effect, through which vector droplets briefly contact the air bubble surface and subsequently transfer oxygen to the bulk aqueous phase (Alves & Pinho, 2013;Quijano & Hernandez, 2010).…”
Section: The Effect Of Oxygen Vectors On Oxygen Mass Transfermentioning
confidence: 99%
“…Alternatively, spreading hydrocarbons (e.g., n-heptane) generally induce an initial decrease in k L a at low concentrations, followed by a gradual increase in k L a with increasing concentration (Alves & Pinho, 2013;Cents, Brilman, & Versteeg, 2001;Linek & Beneš, 1976;Yoshida, Yamane, & Miyamoto, 1970). An alternate/complementary explanation is that the vector film forming around air bubbles becomes unstable with increasing thickness as the vector concentration increases, resulting in the release of oxygen-rich droplets into the bulk aqueous phase (Alves & Pinho, 2013). An alternate/complementary explanation is that the vector film forming around air bubbles becomes unstable with increasing thickness as the vector concentration increases, resulting in the release of oxygen-rich droplets into the bulk aqueous phase (Alves & Pinho, 2013).…”
Section: The Effect Of Oxygen Vectors On Oxygen Mass Transfermentioning
confidence: 99%